LIBRARY NETWORK: CURRENT TRENDS AND CHALLENGES - Talikoti, Sharanabasappa Charalingappa (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Library networks are integral to the modern information ecosystem, enabling the collaboration and resource-sharing among libraries to enhance access to information and services. This study explores the current trends and challenges in library networks, examining their impact on library operations, user access, and inter-library cooperation. By analyzing recent developments and emerging technologies, this paper aims to provide a comprehensive understanding of how library networks are evolving and the obstacles they face. The study also identifies future opportunities for improving library networks to better serve communities and advance the field of librarianship.